Short-term impact of preschool sound exposure on outer hair cell function in young children: An analysis using pressurised distortion product otoacoustic emissions - Loisa Sandström; Sofie Fredriksson; Elina Mäki-Torkko; Mikael Ögren; Janina Fels; Kerstin Persson Waye (PLoS ONE, 2025)
Background Preschool children are regularly exposed to high noise levels that may affect hearing. A previous study has linked preschool noise exposure to reduced distortion product otoacoustic emission (DPOAE) amplitudes. Since DPOAEs primarily reflect outer hair cell (OHC) activity, they provide an indirect marker of cochlear function. Measurement accuracy can be affected by middle-ear pressure. Pressurised DPOAEs (pDPOAEs) compensate for middle-ear pressure during recording. Methods This cross-sectional study aimed to examine the relationship between preschool noise exposure and pDPOAE amplitudes while accounting for middle-ear pressure. Seventy-five children (4–6 years old) were monitored using dosimeters to measure the equivalent continuous sound level (L AeqTi) and the 95th percentile of maximum levels (L AFmax,95). Of these, 56 children completed pDPOAE testing at four time points during the preschool week. Linear mixed-effects models evaluated associations with noise exposure, time of day and progression across the week. Results For personal dosimetry, the mean L AeqTi was 80 dB (range: 60–98 dB) and the mean L AFmax,95 was 97 dB (range: 77–110 dB). Most L AeqTi levels (86.2%) were between 75–85 dB, with L AFmax levels exceeding 115 dB in 53.8% of the cases. No significant associations were found between L AeqTi or L AFmax,95 and pDPOAE amplitudes (p > 0.05). Time-of-day differences were observed, with higher amplitudes in the afternoon at 4 kHz (p = 0.045) and 6 kHz (p = 0.047) in the right ear, and 3 kHz in the left ear (p = 0.021). Girls showed higher amplitudes than boys at 4 kHz in the left ear (p = 0.030). Conclusions Although pDPOAE amplitudes varied with time of day, and sex, a direct exposure–response relationship with preschool noise was not demonstrated. Short-term variations in typical preschool noise exposure may not measurably affect cochlear function in young children. Future research should refine exposure assessment and recording protocols to reduce variability and improve detection of small physiological changes.